Utilization of Sea Cucumber (Holothuria scabra) for Nutritious and Healthy Food Consumption in the Maluku Community - Tuaputty, Hasan; Leiwakabessy, Fredy; Wael, Syahran (RUMPHIUS, 2025)
Types of sea cucumbers consumed by communities in the Maluku region are primarily Bohadschia bivittata, Holothuria scabra, and Pentamera calcigera, which are found in sandy substrates, hence referred to as "sandy sea cucumbers." Proximate analysis results show the highest protein content at 6.19% in Pentamera calcigera and the lowest at 5.24% in Holothuria scabra. The highest fat content is 0.71% in Bohadschia bivittata, and the lowest is 0.55% in Pentamera calcigera. The highest ash content is 3.29% in Bohadschia bivittata, and the lowest is 3.10% in Pentamera calcigera. The highest moisture content is 90.65% in Bohadschia bivittata, while Holothuria scabra has nutritional values between the other two species. A significant relationship exists between knowledge and skills in managing nutritious meal preparation, as indicated by an R² value of 0.961. This suggests that 96.1% of the community's skill in preparing nutritious and healthy meals from sandy sea cucumbers is influenced by their knowledge, with only 3.99% attributed to other factors. In other words, the higher the community's knowledge about sea cucumbers as a nutritious and healthy food source, the better their skills in preparing nutritious meals.